Relationship between procalcitonin levels and presence of vesicoureteral reflux during first febrile urinary tract infection in children - İpek, İlke Özahi; Sezer, Rabia Gönül; Şenkal, Evrim; Bozaykut, Abdulkadir (Elsevier, 2012)
OBJECTIVE To investigate the association between the procalcitonin (PCT) level during the first febrile urinary tract infection (UTI) in children and the presence of vesicoureteral reflux (VUR). VUR-associated UTI is among the primary causes of chronic renal failure in Turkey. METHODS From March 2008 to November 2009, patients admitted with their first febrile UTI were included in the present prospective hospital-based study. The serum concentrations of C-reactive protein, complete blood count, and PCT were measured. All patients underwent renal ultrasonography and voiding cystourethrography. RESULTS Of the 66 patients who were diagnosed with UTI, 18 had VUR. The geometric mean of the PCT levels was significantly greater in the children with VUR than in those without (P = .006). After logistic regression adjustment, the association between the PCT levels and the presence of VUR remained significant (odds ratio 5.08, 95% confidence interval [CI] 1.43-18.02). A PCT level >0.56 ng/mL had 66.7% sensitivity (95% CI 41-86.6) and 77.1% specificity (95% CI 62.7-88) for diagnosing VUR. The area under the receiver operating characteristic curve for PCT was 0.715 (95% CI, 0.56-0.86, P = .007), and the area under the curve for C-reactive protein was 0.723 (95% CI 0.58-0.86, P = .006). CONCLUSION A PCT-guided strategy could help in detecting patients with VUR. Large cohort studies are needed to define an accurate cutoff value for children who are at risk of VUR, which increases the risk of renal damage and subsequent scarring.
WOS: 000302792500042
PubMed ID: 22245305
Keywords: Reflux During; Febrile Urinary; Procalcitonin Levels; Children